Mutu Organoleptik Telur Ayam Ras Menggunakan Rempah Serai (Cymbopogon Citratus) - Supamri Supamri; Ibrahim Ibrahim (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2020)
The purpose of this study was to determine the influence of kitchen lemongrass spice (Cymbopogon citratus) on the organoleptic quality of purebred chicken eggs. In accordance with the objectives of the research to be achieved, then in the analysis using the Complete RandomIzed Design (RAL) consisting of 3 treatments namely T 1 = 1 week, T 2 = 2 weeks and T 3 = 3 weeks with repeated as many as 5 times so that 15 experimental units were obtained. The results showed the influence of kitchen lemongrass spice (Cymbopogon citratus) on the organoleptic quality of purebred chicken eggs in the color, aroma, and appearance criteria test and hedonic test did not give a real influence (P>0.05). In conclusion, the use of lemongrass spice does not give a noticeable influence on the organoleptic quality of purebred chicken eggs. Keywords: Purebred chicken eggs, Lemongrass Spice (Cymbopogon citratus), Organoleptic Quality